2020
DOI: 10.1039/d0cc03325a
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous photocatalytic anaerobic oxidation of alcohols to ketones by Pt-mediated hole oxidation

Abstract: We report a platinum nanocluster/graphitic carbon nitride (Pt/g-C3N4) composite solid catalyst with photocatalytic anaerobic oxidation function for highly active and selective transformation of alcohols to ketones. The desirable products were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Therefore, developing visible‐light active photocatalysts for LDAS is highly desired. Several visible‐light active semiconductors such as CdS, [29,30,74] CdS x Se 1‐x , [74] and graphitic carbon nitride [31,32] have been modified with metal particles for catalyzing LDAS. In particular, it has been shown that Ni‐modified CdS (Ni/CdS) can efficiently split a variety of alcohols into H 2 and corresponding carbonyl compounds in a stoichiometric manner under irradiation of visible light [29] …”
Section: A Brief Development History Of Ldasmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, developing visible‐light active photocatalysts for LDAS is highly desired. Several visible‐light active semiconductors such as CdS, [29,30,74] CdS x Se 1‐x , [74] and graphitic carbon nitride [31,32] have been modified with metal particles for catalyzing LDAS. In particular, it has been shown that Ni‐modified CdS (Ni/CdS) can efficiently split a variety of alcohols into H 2 and corresponding carbonyl compounds in a stoichiometric manner under irradiation of visible light [29] …”
Section: A Brief Development History Of Ldasmentioning
confidence: 99%
“…Loading metal particles on the surfaces of semiconductors can significantly enhance the activity of the pure semiconductors in LDAS, which could be attributed to the formation of the Schottky barrier [46,48] and the catalytic properties of the metals. The metal particles, also called co‐catalysts, are transition metals such as Pt, [32,65,66,71,74,75] Pd, [32,74,75] Ru, [32,75] Au, [67,69] Ni [29,30,63,73] . Their crystal structures are usually face‐centered cubic (fcc) structures (Figure 2).…”
Section: Heterogeneous Photocatalysts For Ldasmentioning
confidence: 99%
See 3 more Smart Citations